Incidence of pneumococcal disease in children in Germany, 2014-2019: a retrospective cohort study - Jessica Weaver; Tianyan Hu; Bélène Podmore; Rosemarie Barnett; Dominik Obermüller; Wolfgang Galetzka; Nawab Qizilbash; Dennis Haeckl; Thomas Weiss; Salini Mohanty; Meghan White; Timo Boellinger (BMC, 2024)
Abstract Background Novel, expanded valency pneumococcal conjugate vaccines (PCVs) are in development to reduce the burden of pneumococcal disease (PD) in children. To understand the potential value of new vaccines in Germany, this study estimated the residual burden of PD in children < 16 years old from 2014 to 2019, using administrative health data from a large German claims database. Methods Outpatient and inpatient cases of all-cause pneumonia (ACP), pneumococcal pneumonia (PP) and invasive pneumococcal disease (IPD) were identified in the InGef database. Incidence rates (IRs) with 95% confidence intervals (CI) were calculated as number of episodes/person-years (PY) at risk. The Mann-Kendall test assessed time trends in incidence. Results There were no significant trends in IRs of IPD or PP from 2014 to 2019. For ACP, IRs declined from 2014 to 2019; 2,213 (CI 2,176-2,250) to 1,503 (CI 1,472-1,534) per 100,000 PY (p = 0.017). IRs of ACP and PP were highest among children aged 12-23 months; 4,672 (CI 4,584-4,762) and 20.8 (CI 15.3-27.5) per 100,000 PY, respectively. For IPD, children 5-11 months-old had the highest IRs, at 14.7 (CI 9.0-22.7) per 100,000 PY. Conclusions From 2014 to 2019 there were no discernible trends in the IRs of PP or IPD, but the IRs of ACP declined in children aged < 16 years. The highest IRs of ACP, PP and IPD were observed in children < 2 years of age, highlighting the importance of infant pneumococcal vaccination in the prevention of pediatric PD. The clinical burden of pediatric PD in Germany persists. Continued surveillance of changing pneumococcal burden, serotype distribution, antimicrobial resistance and vaccination status is critical to better understand the factors driving incidence of PD and to inform future vaccination strategies.